Menelusuri Jejak Ekonomi dan Ekologi: Trade of Perluasan Perkebunan Sawit di Sumatera Utara - Lisna Berutu; Rodiatul Husna; Ahmad Pramanda; Eka Indra; Sari Wulandari (Pusat riset dan Inovasi Nasional, 2025)
Oil palm plantations are a strategic sector in economic development in North Sumatra, Indonesia. This study aims to analyze the economic and ecological impacts of oil palm plantation expansion and evaluate the balance between benefits and disadvantages caused. The descriptive qualitative method is used by utilizing secondary data from the Central Statistics Agency, environmental organization reports, and academic studies. The results show that the expansion of oil palm plantations makes a significant contribution to increasing regional income and job creation. However, land expansion without sustainable management leads to deforestation, loss of biodiversity, deterioration of the quality of water resources, and microclimate and local weather changes. To overcome these challenges, sustainable management policies that integrate agroforestry principles and strict supervision are needed to maintain a balance between economic development and environmental conservation.